Proxy WHO Disability Assessment Schedule 2.0 Is Clinically Useful for Assessing Psychosocial Functioning in Severe Mental Illness - Koopmans, Anne B.; van Hoeken, Daphne; Clarke, Diana E.; Vinkers, David J.; van Harten, Peter N.; Hoek, Hans W. (Frontiers in Psychiatry, 2020)
Aims: This study explores how well the World Health Organization Disability Assessment Schedule (WHODAS 2.0) assesses problems with psychosocial functioning in patients with severe mental illness (SMI). Further, we assessed the relationships between psychosocial functioning and psychopathology, medication side effects, treatment setting, and quality of life. Methods: We performed an observational, cross-sectional study on the island of Curaçao to assess psychosocial functioning in 77 patients with SMI; they mainly had psychotic disorders. We interviewed their healthcare providers using the proxy version of the WHODAS 2.0. In addition, patients were examined for psychiatric symptoms, medication side effects (including drug-induced movement disorders), and quality of life. Associations were examined with Spearman’s rank correlation (ρ). Results: Difficulties in psychosocial functioning were reported by patients with SMI in the WHODAS 2.0 domains of Understanding and communicating (Mean (M)=34.5, standard deviation (SD)=18.6), Participation in society (M=25.5, SD=15.6), and Getting along with people (M=24.1, SD=16.1). Notably, outpatients had more problems participating in society than inpatients (M=33.6, SD=18.5 versus M=23.2, SD=14.1, p=0.03). A positive correlation was observed between drug-induced parkinsonism and the WHODAS 2.0 total score (ρ =0.30; p=0.02), as well as with various subscales, getting around and household activities. Conclusion: The proxy version of the WHODAS 2.0 is clinically useful for patients with severe mental illness. The highest scores on the WHODAS 2.0 were found in domains related to interactions with other people and to participation in society. Inpatient status appeared to aid participation in society; this might be due to living in the sheltered clinic environment and its associated daily activities. We further found that drug-induced parkinsonism was associated with a broad spectrum of psychosocial disabilities.